Representações da maternidade em contos da Literatura Brasileira Contemporânea - Silveira, Andresa da (2022)
Historically, the mother figure has been idealized based on the myth of unconditional and unshakable maternal love, which is related to several social, economic and religious interests. Certain that the theme is an issue that directly impacts the intellectual and physical emancipation of women, the present work intends to reflect on the representations of the mother figure in short stories from contemporary Brazilian literature, contrasting them with socially imposed stereotypes of women. Moreover, it seeks to analyze whether the social impositions are presented in the same way for all women, based on the diversity of their experiences, ethnicities and contexts in which they are inserted, both in literary narratives and in society. In order to investigate how the maternal image was constructed and to understand how it is established until today, the studies of feminist theories are used as a theoretical basis and as an instrument of critical investigation. The literary tales examined, which are by contemporary writers Clarice Lispector, Conceição Evaristo and Giovana Madalosso, respectively from the works Laços de Família, Olhos D'água and A teat rational, deal with issues about maternity that surround women from the middle ages to the current period. In the respective narratives, there are discussions about motherhood that do not meet the standards that society considers as the ideal mother. Based on this, there is a need for motherhood to be analyzed and discussed as a plural experience.